2023
DOI: 10.53664/jsrd/04-01-2023-12-133-145
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Decision Making of Retail Investors in Pakistan Stock Exchange: A Comprehensive Analysis of Key Factors

Abstract: In recent years, field of behavioral finance has gained increasing attention, with numerous studies investigating impact of various factors on investors' decision-making. However, there remains a critical gap in literature when it comes to a comprehensive understanding of the factors that influence retail investors' decision-making. This gap presents a chance for further research to explore factors that affect retail investors' decision-making, particularly in developing nations like Pakistan. The study examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Risk tolerance refers to an investor's willingness to take on risk or uncertainty in their investment choices. It plays crucial role in shaping the investment behavior and act as a mediator between various factors and investment decisions (Khurshid & Ahmad, 2023). Hussain et al (2017) identified three heuristics that expectedly influence investors' decisions, with higher-educated and more experienced investors being less susceptible to these heuristics.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Risk tolerance refers to an investor's willingness to take on risk or uncertainty in their investment choices. It plays crucial role in shaping the investment behavior and act as a mediator between various factors and investment decisions (Khurshid & Ahmad, 2023). Hussain et al (2017) identified three heuristics that expectedly influence investors' decisions, with higher-educated and more experienced investors being less susceptible to these heuristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The importance of institutional and individual investors in Pakistan's stock market should not be underestimated (Ahmad, 2017). Although institutional investors have larger portfolios compared to retail investors, understanding retail investors is vital as they have disproportionate impact when shared (Khurshid & Ahmad, 2023). Those studying financial markets often assume that the institutional investors are better informed and actively counteract excessive interest of retail investors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations